2014
DOI: 10.1103/physrevd.90.045008
|View full text |Cite
|
Sign up to set email alerts
|

SO(10) grand unified theories with dynamical Yukawa couplings

Abstract: Renormalizable SO (10)

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…In such NMSGUT based models, however, the Higgs and Yukawon functions can be comfortably combined, without sacrificing renormalizablity, and the flavour symmetry broken at the only scale where there is a hint of flavour unification : the GUT scale. In [20,21] we showed that this economical scenario is actually realizable in the context of models where a gauged O(N g ) flavour symmetry is appended to the NMSGUT without disturbing the structure of NMSGUT apart from the promotion of Higgs from bland to flavoured and the inverse demotion of SO (10) matter Yukawas from flavoured to to bland. We note that the freedom to gauge flavour achieved in these models is in line with the philosophy we have consistently abided by, first in MSLRMs [4] and then in MSGUTs [13,14,10,16,17] : invoke no ad hoc global symmetries whether continuous or discrete and shelter always under the sole reliable dynamical principle revealed by 20th century physics : local gauge invariance.…”
Section: Yukawon Flavour Modelsmentioning
confidence: 92%
See 3 more Smart Citations
“…In such NMSGUT based models, however, the Higgs and Yukawon functions can be comfortably combined, without sacrificing renormalizablity, and the flavour symmetry broken at the only scale where there is a hint of flavour unification : the GUT scale. In [20,21] we showed that this economical scenario is actually realizable in the context of models where a gauged O(N g ) flavour symmetry is appended to the NMSGUT without disturbing the structure of NMSGUT apart from the promotion of Higgs from bland to flavoured and the inverse demotion of SO (10) matter Yukawas from flavoured to to bland. We note that the freedom to gauge flavour achieved in these models is in line with the philosophy we have consistently abided by, first in MSLRMs [4] and then in MSGUTs [13,14,10,16,17] : invoke no ad hoc global symmetries whether continuous or discrete and shelter always under the sole reliable dynamical principle revealed by 20th century physics : local gauge invariance.…”
Section: Yukawon Flavour Modelsmentioning
confidence: 92%
“…The spontaneous symmetry breaking at the GUT scale due to the above superpotential is largely analogous to the MSGUT case although algebraic complications require numerical solution of the F term conditions [20]. The contribution of the MSGUT type Higgs fields to the flavour group D terms cannot vanish and this breaks supersymmetry unless additional chiral multiplets charged under flavour but not under SO(10) and free to cancel the MSGUT type Higgs contribution in the flavour D-Terms are introduced.…”
Section: Yukawon Flavour Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Continuous flavor symmetries have been previously discussed in, for instance, Refs. [16][17][18][19][20][21][22][23][24][25][26]. Under Flavorspin, quarks and leptons transform as triplets and Yukawa matrices are upgraded to composite spurions, formed by linear combinations of fundamental ones that transform as symmetric or antisymmetric real matrices under flavor SU (2).…”
Section: Introductionmentioning
confidence: 99%